High school students’ mathematical representation ability: Evaluation of disposition based on mastery learning assessment model (MLAM) - Rani Darmayanti; Mohammad Syaifuddin; Nopia Rizki; Rahmad Sugianto; Niswatun Hasanah (CV. FOUNDAE, 2022)
Mathematical representation is the ability of students to explore and use mathematical ideas explicitly. This study aimed to learn about the effectiveness of the Mastery Learning Assessment Model (MLAM) in mathematics learning at the Assyfa Learning Center Foundation Pasuruan, which then described students' abilities in solving mathematical representation problems evaluated from mathematical dispositions. MLAM is based on repeating a similar assessment through an overhaul of mastery learning from previous researchers. This study used a descriptive qualitative method. In the study presented here, 20 subjects were pooled and surveyed using a continuous assessment tool based on high, low, and moderate math ability. The results showed that almost all students could use representational images to solve mathematical problems, create mathematical models, and solve problems related to mathematical expressions. On the other hand, most students could not complete the two indicators of mathematical representation, namely making sketches and mathematical models based on the given situation and data. This result is indicated by the 75 percent of students who completed this lesson. Based on the Teaching Evaluation (TER) results, most students are also satisfied with this approach. It is expected that the MLAM assessment can improve students' mathematical representation skills.